Numerical simulation of mixing characteristics of CNG-air mixer for dual-fuel vehicle - Muhssen, Hassan Sadah (2016)
A compressed natural gas (CNG)-air mixer is a device like a carburettor positioned at the air intake manifold of the engine to mix CNG with incoming air at proper amounts of CNG and air prior to entering the combustion chamber. According to literature, the best design of CNG-air mixer is one that is able to meet the conditions of 1) supply the engine with a homogeneous mixture of CNG and air, 2) with air and CNG with the required air fuel ratio (AFR), and 3) without reduction of the air intake manifold size. The homogeneous mixture occurs when the uniformity index (UI) of methane mass fraction (MCh4) =1.0. From previous studies, there is no design of CNG-air mixer which could satisfy all the above three conditions at the same time. This research carried out a computational fluid dynamics (CFD) study to design a CNG-air mixer for CNG-diesel dual fuel (DDF) engine. The objectives of this study were to examine the performance of existing Secondary Fuel Premixing Controller (SFPMC) commercial mixer and modify it in terms of air fuel ratio (AFR) and CNGair mixture homogeneity (CAMH). The validity and reliability procedures of the simulation results were carried out using the grid independent test, and verification by comparing the results with the literature. Results from simulation indicated that the original mixer (model 1) was unable to control AFR due to the shaft design of the control valve. Furthermore, this mixer could not provide a homogeneous mixture of CNG and air due to the mixer’s internal design, position and directions of the CNG holes. Therefore, the mixer design was modified in terms of AFR and CNG-air mixture homogeneity. Design modification of the control valve shaft was the first method to control AFR, while the second modification involved removing the control valve and also assuming that the gas flow rate is controlled by the electronic flow controller and electronic control unit (ECU). For the mixture homogeneity, there were 10 alternative designs that were tested (models 2-11) to achieve the desired design. The uniformity index (UI) of methane mass fraction (MCh4) was the approach used to quantify CNG spread on the mixer outlet. The UI of MCh4 represents how MCh4 varies over a plane surface, where a value of 0 and 1 indicate the lowest and highest uniformity of gas spread, respectively. Based on the results obtained from mixer models 1-11, it can be concluded that models 8 and 11 showed a superior performance in terms of UI. The minimum UI of MCh4 at the outlet of these two mixer models was not less than 0.96 at various engine speeds of 1000, 1500, 2000, 3000, and 3600 rpm, and 0.87 at various AFRs of 10, 17.2, 20, 30, and 40. On the other hand, at the outlet of original mixer, the maximum UI of MCh4 was not higher than 0.57 at various engine speeds, and 0.58 at various AFRs. In terms of AFR, the optimized mixer with a new control valve shaft showed better controlling of AFR at the various engine speeds compared with the original mixer.